Role of short interpregnancy interval, birth mode, birth practices, and the postpartum vaginal microbiome in preterm birth - Odogwu, Nkechi Martina (Frontiers in Reproductive Health, 2023)
There have been widely documented beneficial role of vaginal Lactobacillus species as an important biomarker for vaginal health and healthy pregnancy progression. When translating this to clinical settings, pregnant women with low proportions of Lactobacillus and commensurately high proportion of rich and highly diverse abnormal microbiota are most likely to encounter negative pregnancy outcome such as preterm birth and postpartum complications. However, multiple literatures have also addressed this notion that the absence of a Lactobacillus-dominated microbiota does not appear to directly imply to a diseased condition and may not be a major determinant of negative obstetric outcome. Caesarian delivery is notably a risk factor for preterm birth and postpartum endometritis, yet recent data shows a trend in the overuse of CS across several populations. Growing evidence suggest the potential role of vaginal/uterine cleaning practice during CS procedures in influencing postpartum infections, however there is a controversy that this practice is associated with increased rates of postpartum endometritis. The preponderance of bacterial vaginosis associated bacteria vagitype at postpartum which persist for a long period of time even after lochia regression in some women may suggest why short interpregnancy interval may pose a potential risk for preterm birth. While specifically linking an exact causative infectious agent to preterm birth and postpartum pathologies remains elusive, clinical attention should also be drawn to the potential contribution of other factors such as short interpregnancy interval, birth mode, birth practices and the postpartum vaginal microbiome in preterm birth which is explicitly described in this review.